2021
DOI: 10.3389/fchem.2021.717904
|View full text |Cite
|
Sign up to set email alerts
|

New Polyprenylated Acylphloroglucinol Derivatives and Xanthones From Hypericum wilsonii

Abstract: Four new polyprenylated acylphloroglucinol derivatives, hyperwilone A-D (1–4), and two new xanthones, wilsonxanthone A (5) and wilsonxanthone B (6), together with eight known compounds were isolated from the aerial parts of Hypericum wilsonii. Their structures were expounded by comprehensive analysis of the 1D and 2D NMR spectra and HRESIMS. The relative configurations and absolute configurations of 1-6 were determined by NMR calculations and comparing their experimental and computed ECD data. All compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Then, the NMR calculations performed through the QM-NMR method at the mPW1PW91/6-31G(d) level by the GIAO approach. 19,20 Further DP4+ analyses based on the 13 C NMR data indicated (12 S *)- 4a ( R 2 = 0.9980) was the correct structure with 100% probability (Fig. 5) Furthermore, the absolute configuration of 4 (12 S ) was determined by comparative analysis of calculated and experimental ECD spectra (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Then, the NMR calculations performed through the QM-NMR method at the mPW1PW91/6-31G(d) level by the GIAO approach. 19,20 Further DP4+ analyses based on the 13 C NMR data indicated (12 S *)- 4a ( R 2 = 0.9980) was the correct structure with 100% probability (Fig. 5) Furthermore, the absolute configuration of 4 (12 S ) was determined by comparative analysis of calculated and experimental ECD spectra (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[ 1‐2 ] It was found that isoprenylated xanthones were another kind of characteristic components in the study of PPAPs from the genus Hypericum . [ 3‐4 ] Isoprenylated xanthones are a kind of natural products with a dibenzo‐ γ ‐pyrone scaffold from benzoylated phloroglucinol and substituted with isopentenyl groups. Their structures varied due to the hydrogenated xanthone core as well as the oxidation and cyclization of isopentenyls to create novel caged xanthone derivatives.…”
Section: Background and Originality Contentmentioning
confidence: 99%